Occurrence, spatiotemporal variation, source, and risk of organophosphate triesters and diesters in soil of e-waste dismantling parks - Wenya Yang; Feng Zhang; Qiubing Ma; Xuwenqi Zhang; Minmin Hou; Xiaoling Jin; Feihang Xu; Jie Lin; Pengfei Li; Baofeng Zhang; Yali Shi; Yaqi Cai (Environmental Research, 2026)

Efficient biosynthesis of limonene from sugarcane molasses using engineered yeast - Shengliang Cai; Xiaoyuan Wang; Jingtao Zhou; Chengcheng Yuan; Xiaoling Lin; Lan Wei; Dongying Chen; Pingxu Chen; Chaoyi Zhu; Shuang Li (Biomass and Bioenergy, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Increased precipitation partially alleviates the carbon–water tradeoff under the Grain for Green program - Liang Zheng; Hao Wu; Jianzhong Lu; Jianshu Wang; Tinghui Li; Anqi Lin; Xiaoling Chen (Environmental Research, 2026)

Tidal pumping modulates the dissolved organic carbon dynamics and exchange fluxes across the mangrove-fringed estuary-coast interface in Zhanjiang Bay, China - Peng Zhang; Jia Lei; Lin Zhou; Xiaoling Chen; Haowen Yu; Qing Ye; Kaixin Huang; Jibiao Zhang (Marine Environmental Research, 2026)

Pharmacogenomic screening strategy and indicative screening efficiency for antithyroid drug-induced agranulocytosis in the Southern Han Chinese - Li Ma; Sujie Ke; Peiji Huang; Yao Chen; Qian Lin; Menghua Lin; Guanlian He; Laiyu Zou; Xiaoling Chen; Xiaoying Liu; Libin Liu; Lijing Wang (European Journal of Clinical Pharmacology, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Mechanically engineered multi-oxide heterojunctions for bifunctional antibacterial and photocatalytic environmental remediation - Juan Pei; Jialan Mi; Shuhan Yao; Mingxing Guo; Ye Zhang; Xiaoling Wan; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Haichun Zeng; et al. (Journal of Environmental Chemical Engineering, 2026)

Microplastic entry into bloodstream via hemodialysis: A dual-simulation clinical study - Yao Deng; Taoping Sun; Zhenheng Long; Xiaoling Luo; Xuyang Geng; Zefang Lin; Chunzhao Chen; Xiaoliang Li (Environmental Pollution, 2026)

Research on the application of nanopore sequencing technology in investigating microbial data deviation - Xiaoling Zheng; Hongxia Yang; Wanzi Gong; Shiyu Wang; Yinhuan Wang; Deyin Deng; Tingzhang Wang; Hong Li; Chenshui Lin (Antonie van Leeuwenhoek, 2026)

Pericyte NNMT drives an immune-hostile vascular niche and restricts cancer immunotherapy - Sheng Wang; Geni Ye; Caiyun Zhang; Lin Tan; Zhang Zhang; Xi Xu; Xinhui Chen; Yiming Zhang; Xiaoling Xu; Jinghua Pan; Tong Lan; Junqiu Zhang; et al. (Science Bulletin, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Metal-modified nitrogen self-doped biochar as an electrode plate for electrocatalytic removal of methylene blue - Guanbiao Ruan; Yuehong Yang; Junya Wang; Gaoyuan Qin; Xiaoling Peng; Daozhao Lin (Journal of Environmental Management, 2026)

Nonagricultural emissions and N2O5 hydrolysis drive wintertime inorganic nitrogen aerosol formation in Sichuan Basin: Nitrate and ammonium isotopic evidence - Xiaojuan Huang; Yuhan Long; Yuepeng Pan; Lin Han; Xiaoling Zhang; Junke Zhang; Runqi Zhang; Yingjun Chen; Jianmin Chen (Journal of Hazardous Materials, 2026)

Effects of Deep Learning Bias Correction and Carbon Neutrality on Projections of Future Population Exposure to Extreme Precipitation - Xiaohua Xiang; Wenbin Wang; Xiaoling Wu; Zhu Liu; Adnan Rajib; Lei Wu; Hongwei Cao; Xian Lin; Yuan Liu (International Journal of Climatology, 2026)
Spatiotemporal variations in extreme precipitation and their impacts on population exposure remain poorly understood due to biases in climate model projections and assumptions inherent in emission scenarios. In this study, we evaluate the bias‐correction performance of three deep learning techniques—Convolutional Neural Networks (CNN), Long Short‐Term Memory networks (LSTM), and hybrid CNN‐LSTM—using extreme precipitation indices derived from 10 Coupled Model Intercomparison Project Phase 6 (CMIP6) models. Building on this, we assess exposure for China's nine river basins under Shared Socioeconomic Pathway (SSP)1–2.6 and SSP3–7.0 in the near future (2031–2060) and far future (2071–2100) and quantify the potential benefits of achieving carbon neutrality on reducing population exposure to extreme precipitation. Our findings reveal that CNN outperforms both LSTM and CNN‐LSTM in correcting biases. Compared to the historical period (1985–2014), both R95p and Rx1day exhibit increasing trends across China at the scenario and temporal levels. The SSP3–7.0 scenario shows more pronounced increases than SSP1–2.6, and the long‐term trends (2071–2100) are greater than those observed in the short‐term period (2031–2060). Spatially, the strongest responses are observed in the southwest and southeast coastal regions, while changes in inland areas are more moderate. On the exposure side, SSP3–7.0 results in a substantial national increase, with far‐future exposure projected to reach approximately 2.7 times the near‐future levels for Rx1day and 1.2 times for R95p. Hotspot areas of exposure are found along the Yangtze–Pearl River Delta–Southeast coastal belt, the southwestern uplands, and the Beijing–Tianjin–Hebei–Bohai corridor. In contrast, the carbon‐neutral pathway (SSP1–2.6) leads to approximately 80% reductions in national exposure in the far future, with reductions greater than 70% in all nine basins. We suggest that climate extreme changes, rather than population dynamics or extreme‐population interactions, are anticipated to dominate these reductions in the future. These results provide important scientific support for ongoing efforts aimed at achieving carbon neutrality by the 2060s to reduce the potential risk of extreme precipitation in China and its nine major river basins.

In vitro digestion, cellular uptake and absorption of walnut protein-based nanoparticles mediated coenzyme Q10 nanosuspensions - Xiaoling Lin; Pedro Rodriguez Gonzalez; Dganit Danino; Harold Corke (Food Hydrocolloids, 2025)

Mechanochemical synthesis of ZnO@TiO2 II heterojunction material: Photocatalytic degradation and antibacterial synergistic effect - Juan Pei; Xiaoling Wan; Mingxing Guo; Jialan Mi; Wei Wu; Ying Hong; Pei Hu; Ping Chen; Lin Chen; Siwei Xiang; Qianyu Zhang; Haichun Zeng; et al. (Chemical Engineering Journal, 2025)

Adsorption behavior of methane in thermally altered coals: A molecular simulation study - Yungang Zhao; Xiaoling Wang; Zeyu Dong; Yuhan Lin (Fuel, 2025)

Mechanistic elucidation and catalyst design of Fe-doped ZnCo2O4 spinels for oxygen vacancy–mediated PMS activation - Xiaoling Lin; Yujia Zhao; Liang Zhang; Yingyi Li; Shangru Zhai; Shuang Shan; Hong Guo; Xianquan Li (Chemical Engineering Journal, 2025)

Identification of Mitochondrial and Succinylation Modification-Related Gene Signature in Ischemic Stroke - Lixia Wang; Jishuai Zhao; Hui Cai; Xiaoling Ying; Yonglei Liu; Zeming Luo; Heyan Chen; Lin Yang (Molecular Neurobiology, 2025)

Seismicity, faulting, and the magmatic fluid influence: Insights from the 2023 ML5.4 earthquake sequence in the Beibu Gulf - Xiaoling Xie; Jiangnan Lin; Yiming Liu; Hui Zhang; Huilin Wang (Tectonophysics, 2025)

Effect of epigallocatechin-3-gallate modification on the structure, hydrophilicity and Pickering emulsion stability of rice bran protein-polysaccharide-phenol natural complex - Helin Li; Xiaojuan Wu; Lizhong Lin; Xiaoling Zhou; Wei Wu (Food Chemistry, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Design of technical Ni@Silicate-1 catalysts for dry reforming of methane - Zhaomin Gao; Mengyang Cai; Jikai Zhang; Jiachen Wang; Chunyan Liu; Peng Guo; Xiaoling Mou; Ronghe Lin; Jiaxu Liu (Chemical Engineering Journal, 2025)

The association between anti-inflammatory therapies and renal outcomes in patients with established cardiovascular disease or high cardiovascular risks: a meta-analysis of randomised controlled trials - Wenfeng Yang; Zonglin Li; Chu Lin; Xiaoling Cai; Fang Lv; Wenjia Yang; Linong Ji (Inflammopharmacology, 2025)

Interleukin-33 modulates NET formation via an autophagy-dependent manner to promote neutrophilic inflammation in cigarette smoke-exposure asthma - Jing Liu; Peizhi Tao; Beiting Su; Li Zheng; Yusen Lin; Xiaoling Zou; Hailing Yang; Wenbin Wu; Tiantuo Zhang; Hongtao Li (Journal of Hazardous Materials, 2025)

Effect of oral Mn-based nanozymes Mn3O4 NPs on morphological, antioxidation, mucosa, and fecal microbial community in mice colons - Baoyue Zhang; Lei Yang; Zhengkun Wu; Xianxiang Wang; Xiaoling Zhao; Wei Zhang; Danqin Li; Hualin Fu; Juchun Lin; Funeng Xu; Xiaoyang Ai; Gang Shu (Food and Chemical Toxicology, 2025)

A review of the current status of nitrogen self-doped biochar applications - Guanbiao Ruan; Yuehong Yang; Xiaoling Peng; Junya Wang; Yongkang Guo; Weiyao Hu; Daozhao Lin (Journal of Environmental Chemical Engineering, 2025)

Unraveling the complexities of ozone and PM2.5 pollution in the Pearl River Delta region: Impacts of precursors emissions and meteorological factors, and effective mitigation strategies - Yating Chen; Liye Zhu; Sihui Wang; Daven K. Henze; Tzung-May Fu; Lin Zhang; Xiaoling Wang (Atmospheric Pollution Research, 2025)

Study on the characteristics of bird communities in urban river corridor parks and green spaces - Yinghong Ding; Dulai Zheng; Yuxin Lin; Junyi Li; Weicong Fu; Ziru Chen; Jin Yang; Xiaoling Xu; Zhipeng Zhu (Environment, Development and Sustainability, 2025)

Intra-seasonal variations of dust activity over East Asia in spring 2023 and their mechanisms - Xiaoling Wu; Chenglai Wu; Zhaohui Lin; Mingzhu Yang (Global and Planetary Change, 2025)

Association between iron status, preeclampsia and gestational hypertension: A bidirectional two-sample Mendelian randomization study - Pengsheng Li; Haiyan Wang; Ting Chen; Gengdong Chen; Zixing Zhou; Shaoxin Ye; Dongxin Lin; Dazhi Fan; Xiaoling Guo; Zhengping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Unraveling size-dependent catalytic activity of monolithic alginate hydrogels for PMS activation and ciprofloxacin removal - Jie Lin; Yunxiong Zeng; Xingyu Zhan; Jingcai Xu; Xinqing Wang; Bo Hong; Xiaoling Peng; Jing Li; Hongwei Chen; Yingchun Xia (Journal of Environmental Chemical Engineering, 2024)

Advancing coenzyme Q10 delivery with plant protein-based nanoparticle-mediated nanosuspensions - Xiaoling Lin; Meier Chen; Pedro Rodriguez Gonzalez; Dganit Danino; Harold Corke (Food Research International, 2024)

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

The predictive value of the neutrophil/platelet ratio on in-hospital adverse events and long-term prognosis in patients with coronary artery disease after percutaneous coronary intervention and its possible internal mechanism - Yifei Xiang; Jilang Zeng; Xueqin Lin; Xiaoling Cai; Liwei Zhang; Manqing Luo; Gengyu Zhou; Xiaofang Chen; Biting Lin; Junhan Chen; fan Chen; Xuan Huang; et al. (Molecular and Cellular Biochemistry, 2024)

Multi-stage perfect load-bearing behavior for tandem honeycomb by face-centered hierarchical strategy - Wenzhen Huang; Yong Zhang; Xiaoli Xu; Junhong Lin; Xiaoling Zhang; Xiang Xu (Engineering Structures, 2024)

The role of exosome derived miRNAs in inter-cell crosstalk among insulin-related organs in type 2 diabetes mellitus - Ting Lu; Ying Zheng; Xiaoling Chen; Zhiyong Lin; Chaoqi Liu; Chengfu Yuan (Journal of Physiology and Biochemistry, 2024)

The association between PM2.5 components and blood pressure changes in late pregnancy: A combined analysis of traditional and machine learning models - Lijie Wang; Li Wen; Jianling Shen; Yi Wang; Qiannan Wei; Wenjie He; Xueting Liu; Peiyao Chen; Yan Jin; Dingli Yue; Yuhong Zhai; Huiying Mai; et al. (Environmental Research, 2024)

Soil warming-induced reduction in water content enhanced methane uptake at different soil depths in a subtropical forest - Lei Zhang; Weisheng Lin; Jordi Sardans; Xiaoling Li; Dafeng Hui; Zhijie Yang; Haizhen Wang; Hao Lin; Yufang Wang; Jianfen Guo; Josep Peñuelas; Yusheng Yang (Science of The Total Environment, 2024)

Effects of rice bran rancidity on the interfacial adsorption properties of rice bran protein fibril aggregates and stability of high internal phase Pickering emulsions - Mengmeng Zhao; Fang Li; Helin Li; Qinlu Lin; Xiaoling Zhou; Xiaojuan Wu; Wei Wu (Food Chemistry, 2024)

Development of gastric digestion-tolerant plant protein-based nanoparticles: Fabrication, characterization, antioxidant activity, and stability - Xiaoling Lin; Can Zhu; Meier Chen; Pedro Rodriguez Gonzalez; Xuanni Chen; Ziwen Zhao; Dganit Danino; Harold Corke (Food Hydrocolloids, 2024)

Flexible and stretchable photodetectors constructed by integrating photosensor, substrate, and electrode in one polymer matrix - Xiaoling Wu; Wenkang Wei; Haimen Lin; Tong Wu; Wenzhen Zheng; Guorong Chen; Weiang Luo; Conghui Yuan; Birong Zeng; Yiting Xu; Lizong Dai (Chemical Engineering Journal, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

IFITM1 and IFITM2 inhibit the replication of senecavirus A by positive feedback with RIG-I signaling pathway - Huizi Li; Ming Chen; Tingting Zheng; Xiaoling Lei; Cunhao Lin; Shuo Li; Jiacong Mo; Zhangyong Ning (Veterinary Microbiology, 2024)

Postharvest treatment with Bacillus velezensis LX mitigates disease incidence and alters the microbiome on kiwifruit surface - Zhihao duan; Huiyun Song; Honghui Shi; Zhu Gao; Jipeng Mao; Yunpeng Cao; Heqiang Huo; Juncheng Li; Xiaoling Wang; Mengfei Lin (Postharvest Biology and Technology, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

The aging behavior of degradable plastic polylactic acid under the interaction of environmental factors - Hui Jiang; Yiqun Wang; Jiaoxia Sun; Yufeng Mao; Sisi Que; Yulian Lin; Yuanyuan Huang; Xiaoling Lei (Environmental Geochemistry and Health, 2024)

Characteristics of the atmospheric boundary layer height: A perspective on turbulent motion - Jinhong Xian; Hongyan Luo; Chao Lu; Xiaoling Lin; Honglong Yang; Ning Zhang (Science of The Total Environment, 2024)

How do residents perceive ecosystem service benefits received from urban streets? A case study of Guangzhou, China - Chongxian Chen; Xiaoling Lin; Yitong Wu; Jiehang Xie; Jingyi Liu (Journal of Cleaner Production, 2024)

Slc43a2+ T cell metastasis from spleen to brain in RGNNV infected teleost - Qing Wang; Yali Liu; Minlin Zhang; Min Yang; Jiantao Liang; Xiaoling Zuo; Shaowen Wang; Xianze Jia; Huihong Zhao; Han Jiang; Qiang Lin; Qiwei Qin (Science China Life Sciences, 2024)

Research on anchoring force of the deep-sea stratum drilling robot - Peihao Zhang; Jiawang Chen; Yongqiang Ge; Xingshuang Lin; Xiaoling Le; Zixin Weng; Ziqiang Ren (Marine Georesources & Geotechnology, 2024)

Spatial distribution of rare earth elements and their impact factors in an area with a high abundance of regolith-hosted deposits - Zhuoling Lin; Yaduo Zhang; Xiaoliang Liang; Guangqing Huang; Fenglei Fan; Xiaoling Yin; Zhihao Chen (Chemosphere, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

A New Approach for Exploring Reperfusion Brain Damage in Hypoxic Ischemic Encephalopathy - Tianlei Zhang; Zhiwei Zhang; Jiayi Geng; Kexin Lin; Xinru Lin; Mengdie Jiao; Jianghu Zhu; Xiaoling Guo; Zhenlang Lin (Molecular Neurobiology, 2024)

Reef effect of vertical relief on the shelter-seeking and foraging processes of juvenile fat greenling (Hexagrammos otakii) in a mesocosm experiment - Yue Zhang; Tao Sun; Gang Ding; Bo Li; Shuhan Li; Wei Yang; Daode Yu; Xiaoling Wang; Qianzhao Sun; Haiying Lin (Applied Animal Behaviour Science, 2024)

Parent and halogenated polycyclic aromatic hydrocarbons exposure in aluminum smelter workers: Serum levels, accumulation trends, and association with health indicators - Chuxuan Zhao; Xiaoling Guan; Qinghua Zhang; Lingling Meng; Wei Lin; Ruiqiang Yang; Yingming Li; Guibin Jiang (Science of The Total Environment, 2024)

Do different types of urban streets lead to varying COVID-19 risk perceptions? An empirical study from a spatial heterogeneity perspective - Yongqi Hou; Chongxian Chen; Xiaoling Lin; Zhitong Zhang; Xinyi Liu; Jiehang Xie; Shaoping Guan (Environmental Impact Assessment Review, 2024)

Exosomal miRNA analysis provides new insights into exposure to nanoplastics and okadaic acid - Linhong Yan; Peichun Lin; Zijie Wu; Zifan Lu; Lihua Ma; Xiaoling Dong; Lei He; Zhenqing Dai; Chunxia Zhou; Pengzhi Hong; Chengyong Li (Science of The Total Environment, 2023)

Land use change alters carbon and nitrogen dynamics mediated by fungal functional guilds within soil aggregates - Chenggang Liu; Yanqiang Jin; Fangmei Lin; Chuan Jiang; Xiaoling Zeng; Defeng Feng; Fuzhao Huang; Jianwei Tang (Science of The Total Environment, 2023)

Understory vegetation management regulates soil carbon and nitrogen storage in rubber plantations - Yan Ren; Fangmei Lin; Chuan Jiang; Jianwei Tang; Zhaofei Fan; Defeng Feng; Xiaoling Zeng; Yanqiang Jin; Chenggang Liu; Olusanya Abiodun Olatunji (Nutrient Cycling in Agroecosystems, 2023)

The combination of multiple linear regression and adaptive neuro-fuzzy inference system can accurately predict trihalomethane levels in tap water with fewer water quality parameters - Jianzhen Zhang; Duo Ye; Quanyou Fu; Minjie Chen; Hongjun Lin; Xiaoling Zhou; Wenjing Deng; Zeqiong Xu; Hongjie Sun; Huachang Hong (Science of The Total Environment, 2023)

Effects of the border on yield and water use in wheat/maize intercropping in rain-fed areas with different nitrogen levels - Zhen Fan; Mingzhu Deng; Yanrong Lin; Pengzhao Liu; Xiaoling Wang; Shengfei Yang; Xiaolong Ren; Xiaoli Chen; Tiening Liu (Field Crops Research, 2023)

Integrated single-cell RNA-seq analysis revealed podocyte injury through activation of the BMP7/AMPK/mTOR mediated autophagy pathway - Hongzhou Lin; Huihui Chen; Rengcheng Qian; Guoqi Tang; Yinjuan Ding; Yalan Jiang; Congde Chen; Dexuan Wang; Maoping Chu; Xiaoling Guo (Chemico-Biological Interactions, 2023)

Understory ferns removal downregulates microbial carbon use efficiency and carbon accrual in previously degraded lands - Cui Deng; Maokui Lyu; Xiaoling Xiong; Josep Peñuelas; Jordi Sardans; Xiaojie Li; Weisheng Lin; Yusheng Yang; Jinsheng Xie (Agricultural and Forest Meteorology, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Exploring in vitro gastrointestinal digestion of myofibrillar proteins at different heating temperatures - Hua Chen; Gaiming Zhao; Xiaoling Yu; Qiuhui Zhang; Chaozhi Zhu; Lin Tong; Jiangang Hao (Food Chemistry, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Chemiluminescence Immunoassay Method of Urinary Liver Fatty-acid-binding Protein as a Promising Candidate for Kidney Disease - Lisong Niu; Lanya Li; Jinshan Li; Zhitian Chen; Jiayuan Lin; Bo Zhang; Xiaoling Fu (Journal of Fluorescence, 2023)

Moderate relative size of covered and non-covered structures of artificial reef enhances the sheltering effect on reef fish - Yue Zhang; Tao Sun; Gang Ding; Daode Yu; Wei Yang; Qianzhao Sun; Xiaoling Wang; Haiying Lin (Frontiers in Marine Science, 2023)
Identifying the relationship between fish aggregations and artificial reefs (ARs) is important for optimizing reef structures and protecting marine resources subjected to external disturbance. Yet, knowledge remains limited of how the distribution of fish is affected by shelter availability provided by different AR structures. Here, we tested the effects of two structural attributes on the distribution of a benthic juvenile reef fish (fat greenling, Hexagrammos otakii ). We used a laboratory mesocosm experiment with a simplified reef unit that was made of covered structure and non-covered structure. The covered structure was defined as the area inside ARs that provided effective shelter. The non-covered structure was defined as the area along the edge of ARs, which attracts fish but has lower sheltering effects. Four scenarios of two orthogonal structural attributes contained in a reef unit were implemented: size of covered structure (small shelter versus large shelter) and size of non-covered structure (small edge versus large edge), forming three size ratios of shelters to edges (low, medium, and high). The sheltering effects of the four scenarios were evaluated based on changes to the distribution patterns of fish under disturbance. We found that the reef with a large shelter had a better sheltering effect than the reef with a small shelter, but was limited by its small edge, especially when fish density was high. In contrast, the sheltering effect of the reef with a small shelter was limited by its large edge compared to the small edge. Thus, a moderate shelter-edge ratio enhanced the ability of juvenile fat greenling to elude external disturbance. Our findings highlight the importance of quantifying how the structural composition of reefs affects fish distributions, providing guidance to optimize AR structures.

The simultaneous removal of NO and SO2 over MnO2 material via the multi-stage fluidized bed process at low temperatures - Changming Li; Xiaoling Zhang; Yunjia Li; Lixin Sun; Lin Huangfu; Jianling Li; Shiqiu Gao; Jian Yu (Fuel, 2023)

Synergistic trimetallic Ni–Cu–Sn catalysts for efficient selective hydrogenation of phenylacetylene - Wei Chen; Huawu Xu; Xiaoling Ma; Lin Qi; Zhiming Zhou (Chemical Engineering Journal, 2023)

PDGFD switches on stem cell endothelial commitment - Weisi Lu; Peipei Xu; Boxiong Deng; Jianing Zhang; Ying Zhan; Xianchai Lin; Xiangzhong Xu; Zhaoxia Xia; Xiaoxi Yang; Xiaoling Zeng; Lijuan Huang; Bingbing Xie; et al. (Angiogenesis, 2022)
The critical factors regulating stem cell endothelial commitment and renewal remain not well understood. Here, using loss- and gain-of-function assays together with bioinformatic analysis and multiple model systems, we show that PDGFD is an essential factor that switches on endothelial commitment of embryonic stem cells (ESCs). PDGFD genetic deletion or knockdown inhibits ESC differentiation into EC lineage and increases ESC self-renewal, and PDGFD overexpression activates ESC differentiation towards ECs. RNA sequencing reveals a critical requirement of PDGFD for the expression of vascular-differentiation related genes in ESCs. Importantly, PDGFD genetic deletion or knockdown increases ESC self-renewal and decreases blood vessel densities in both embryonic and neonatal mice and in teratomas. Mechanistically, we reveal that PDGFD fulfills this function via the MAPK/ERK pathway. Our findings provide new insight of PDGFD as a novel regulator of ESC fate determination, and suggest therapeutic implications of modulating PDGFD activity in stem cell therapy.

Differential Regulation by Mechanical Stretch of the Expressions of Large-Conductance Ca2+-Activated K+ Channel and L-Type Voltage-Dependent Ca2+ Channel in Rat Uterine Smooth Muscle Cells - Xiaoling Jia; Chao Gao; Xia Wang; Lin-Hua Jiang; Yubo Fan (The Journal of Membrane Biology, 2022)

PHD2 attenuates high-glucose-induced blood retinal barrier breakdown in human retinal microvascular endothelial cells by regulating the Hif-1α/VEGF pathway - Jia Li; Xi Lu; Liqing Wei; Dan Ye; Jianqiang Lin; Xiaoyu Tang; Kaixuan Cui; Shanshan Yu; Yue Xu; Xiaoling Liang (Inflammation Research, 2022)

GW10, a member of P450 subfamily regulates grain size and grain number in rice - Penglin Zhan; Xin Wei; Zhili Xiao; Xiaoling Wang; Shuaipeng Ma; Shaojun Lin; Fangping Li; Suhong Bu; Zupei Liu; Haitao Zhu; Guifu Liu; Guiquan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Recent advances in the application of metabolomics for food safety control and food quality analyses - Shubo Li; Yufeng Tian; Pingyingzi Jiang; Ying Lin; Xiaoling Liu; Hongshun Yang (Critical Reviews in Food Science and Nutrition, 2021)

H2S probe CPC inhibits autophagy and promotes apoptosis by inhibiting glutathionylation of Keap1 at Cys434 - Na Li; JuYuan Wang; XiaoLing Zang; ZhaoYang Wang; Tao Zhang; BaoXiang Zhao; JunYing Miao; ZhaoMin Lin (Apoptosis, 2021)

Uncovering the mysterious identity of Taisui—an old Chinese folk legend - Erwei Li; Jinwei Ren; Qian Chen; Hanxing Zhang; Bin Lin; Hui Zhang; Shumin Zhang; Xiaoling Zhang; Lei Cai; Xingzhong Liu (Science China Life Sciences, 2020)

Effects of Plant Diversity and Plant Density on Ecosystem Functions in Floating Constructed Wetlands - Wenjuan Han; Xiaoling Sheng; Jiongni Shao; Jia Jiang; Qinru He; Ying Lin (Water, Air, & Soil Pollution, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Complete genome sequence of a novel recombinant avian leukosis virus isolated from a three-yellow chicken - Tao Sun; Ximei Wang; Wei Han; Xiaoling Ma; Weili Yin; Baohai Fang; Xiao Lin; Yang Li (Archives of Virology, 2020)

A Novel Sediment Pressure Sampling Device Carried by a Hadal-Rated Lander - Jiawang Chen; Yue Huang; Yuan Lin; Peng Zhou; Yuping Fang; Xiaoling Le; Yuhong Wang (Journal of Marine Science and Engineering, 2020)
Reliable sampling technology for deep-sea sediments is a prerequisite for studying the sedimentary environment in the geological history, the mechanical characteristics of sediments and sediment biology. In this study, we develop a new sampling device in order to achieve a convenient and economic pressure sampling for hadal sediments. The overall structure, as well as the key component such as the pressure-holding part, and the sealing structure are designed. The feasibility of the device was verified through field tests. Furthermore, the sampling process is analyzed by the computer simulation. It is found that the sampling length is determined by the open diameter and the installation position of the core keepers. According to the simulation, the structure is optimized, which is beneficial to the further improvement of the sampling length.

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

The Potential of Constructed Wetland Plants for Bioethanol Production - Yan Lin; Yafang Zhao; Xinyi Ruan; Tyler J. Barzee; Zhenyu Zhang; Hainan Kong; Xiaoling Zhang (BioEnergy Research, 2020)

Microbiota analysis revealed vertical transmission and microbial adjusting function of symbiotic fungus in the attelabid weevil fungiculture - Bin Lin; Lin Wang; Muzammil Hussain; Xiaoling Zhang; Jianqing Tian; Sha Qi; Xingzhong Liu; Meichun Xiang (Science China Life Sciences, 2019)

Phosphorus losses under heavy rain from the sloping farmlands in the purple hilly region of Southwestern China - Xiaoling He; Yongdong Wang; Tingxuan Li; Shuqin He; Zicheng Zheng; Xizhou Zhang; Huagang Huang; Haiying Yu; Tao Liu; Chaowen Lin (Journal of Soils and Sediments, 2019)

Toxicological Assessment of Intermediates in Natural Attenuation of p-Xylene to Marine Microalgae - Feng Li; Weiyan Duan; Shuhao Du; Fanping Meng; Xiaoling Peng; Lihong Peng; Yufei Lin; Jiangyue Wu; Guoshan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Transport of colloidal phosphorus in runoff and sediment on sloping farmland in the purple soil area of south-western China - Xiaoling He; Zicheng Zheng; Tingxuan Li; Shuqin He; Xizhou Zhang; Yongdong Wang; Huagang Huang; Haiying Yu; Tao Liu; Chaowen Lin (Environmental Science and Pollution Research, 2019)

Selective, Sensitive and Label-Free Detection of Fe3+ Ion in Tap Water Using Highly Fluorescent Graphene Quantum Dots - Yuanyuan Zhang; Xiangyue Yang; Yunxun Pu; Wei Cheng; Song Lin; Zeyu Shao; Xiaoling Liao (Journal of Fluorescence, 2019)

Identification of two novel chicken GPR133 variants and their expression in different tissues - Kai Tian; Qihai Xiao; Xueyou Zhang; Xi Lan; Xiaoling Zhao; Yan Wang; Diyan Li; Huadong Yin; Lin Ye; Qing Zhu (Functional & Integrative Genomics, 2017)

Secretion of Down Syndrome Critical Region 1 Isoform 4 in Ischemic Retinal Ganglion Cells Displays Anti-Angiogenic Properties Via NFATc1-Dependent Pathway - Yue Xu; Boyu Yang; Yaguang Hu; Lin Lu; Xi Lu; Jiawei Wang; Qinmeng Shu; Qiaochu Cheng; Shanshan Yu; Fan Xu; Jingjing Huang; Xiaoling Liang (Molecular Neurobiology, 2017)

Sequence Analysis and Expression of a Blue-light Photoreceptor Gene, Slwc-1 from the Cauliflower Mushroom Sparassis latifolia - Chi Yang; Lu Ma; Zhenghe Ying; Xiaoling Jiang; Yanquan Lin (Current Microbiology, 2017)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Anti-angiogenic and anti-inflammatory effect of Magnolol in the oxygen-induced retinopathy model - Boyu Yang; Yue Xu; Shanshan Yu; Yongsheng Huang; Lin Lu; Xiaoling Liang (Inflammation Research, 2016)

Blood cadmium burden and the risk of nasopharyngeal carcinoma: a case–control study in Chinese Chaoshan population - Lin Peng; Xiaoling Wang; Xia Huo; Xijin Xu; Kun Lin; Jingwen Zhang; Yue Huang; Kusheng Wu (Environmental Science and Pollution Research, 2015)

Diacylglycerol Kinase (DGK) Inhibitor II (R59949) Could Suppress Retinal Neovascularization and Protect Retinal Astrocytes in an Oxygen-Induced Retinopathy Model - Lu Yang; Yue Xu; Weihua Li; Boyu Yang; Shanshan Yu; Huanjiao Zhou; Cheng Yang; Fan Xu; Jun Wang; Yi Gao; Yongsheng Huang; Lin Lu; et al. (Journal of Molecular Neuroscience, 2015)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

A new furanocoumarin from the mangrove endophytic fungus Penicillium sp. (ZH16) - Zhongjing Huang; Jianxiang Yang; Xiaoling Cai; Zhigang She; Yongcheng Lin (Natural Product Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Impact of air pollution control measures and weather conditions on asthma during the 2008 Summer Olympic Games in Beijing - Yi Li; Wen Wang; Jizhi Wang; Xiaoling Zhang; Weili Lin; Yuanqin Yang (International Journal of Biometeorology, 2011)

Unique evolution characteristics of the envelope protein of EIAVLN40, a virulent strain of equine infectious anemia virus - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Jianhua Zhou (Virus Genes, 2011)

In-situ measurement of atmospheric CFC-11 at the Shangdianzi Global Atmosphere Watch (GAW) Regional Station - Fang Zhang; LingXi Zhou; Bo Yao; XiaoChun Zhang; Lin Xu; XiaoLing Zhang; HuaiGang Zhou; Fan Dong; LiYan Zhou (Science China Earth Sciences, 2011)

Genomic comparison between attenuated Chinese equine infectious anemia virus vaccine strains and their parental virulent strains - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Xiangang Kong; Jianhua Zhou (Archives of Virology, 2011)

Genomic analysis of an effective lentiviral vaccine-attenuated equine infectious anemia virus vaccine EIAVFDDV13 - Xu Qi; Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Rongxian Shen; Fenglong Wang; Xiangang Kong; Zhiqiang Su; et al. (Virus Genes, 2010)

Sequencing, annotation and comparative analysis of nine BACs of giant panda (Ailuropoda melanoleuca) - Yang Zheng; Jing Cai; JianWen Li; Bo Li; Runmao Lin; Feng Tian; XiaoLing Wang; Jun Wang (Science China Life Sciences, 2010)